A Survey Study Assessing Opinions, Knowledge and Training Needs of Physicians Concerning the Field of Transgenic Foods - Vieira, Isabella (2020)
Introduction: Transgenic (genetically modified) foods are being grown, sold and eaten in Portugal. As such it is important that physicians stay up to date on any negative health consequences of such foods. This study aimed to identify their opinion, knowledge and training needs regarding transgenic foods.Material and Methods: A total of 278 physicians responded to a surveyResults: In terms of opinion, 85.8% of physicians had a neutral position, 12.5% had a negative view and a minority (1.7%) was positive. However, 79.8% had a low level of knowledge, 17.7% had an average level of knowledge and only 2.5% showed a high level of knowledge regarding the subject. It should be noted that 91.4% of physicians consider that it is useful to carry out some kind of training during their university education and 65.1% said that it would be very useful during the professional life to have continuing education concerning the issue. Most physicians (83%) could be grouped together according to their interest in learning more. The other group (17%) showed lack of interest.Discussion: Physicians are considered reliable sources, to whom the general population can turn to in order to access valuable health information, which suggests the need to stay up-to-date regarding transgenic foods.Conclusion: This is a pioneering study on Portuguese physicians and transgenic foods. Results point to a need for specific training concerning this issue.